International perspectives on the role of technology in humanizing higher education - Sengupta, Enakshi; Blessinger, Patrick; Makhanya, Mandla (Innovations in higher education teaching and learning, 2020)
The debate around how to maximize the use of technology in education is ongoing, and embedded in the argument that successful inculcation of knowledge cannot happen only by improving the curriculum. But what role does technology play in humanizing higher education? How can it facilitate the kind of all-round development, beyond the classroom, which allows students to create a positive impact on social welfare and community wellbeing? The authors of this volume address the humaneness that surrounds the world of technology in education. By highlighting the use of emerging technologies in pedagogy and drawing on real-life case studies, they address the ongoing debate that technology brings a positive effect on education and beyond. More important than ever as mankind faces unprecedented challenges to classroom-based education, and the demand for technology grows, the authors demonstrate how technology continues to fulfil the challenges of creating a more democratic educational environment.